Implementation of Patient Safety in Hospital during The Covid-19 Pandemic - Iman Permana; Winny Setyonugroho; Budi Susatia; Maryanur Ekanila (Health Notions, 2022)
Background: The first case of Corona Virus Disease (Covid-19) was discovered in Wuhan, China which caused new burdens and challenges to the health system and healthcare workers, including the implementation of patient safety. This study aimed to find out how to implement patient safety in Hospitals during the Covid-19 pandemic. Methods: Relevant articles were obtained from PubMed and SAGE Journals between 2019-2021. This article was chosen to meet the criteria for discussing patient safety in hospitals during the COVID-19 pandemic. Results: A total of 28 from 305 articles were analyzed in this review. The Implementation of patient safety during the COVID-19 pandemic can be through initial screening, use of technology, reducing the risk of transmission, physical adjustment of hospital buildings, personal protective equipment for all, and support systems. Conclusion: Adjustment of all service activities in hospitals, especially during the COVID-19 pandemic, is the most important thing to improve the quality of the service itself. Efforts made in implementing patient safety are aimed at keeping patients and health professionals safe Keywords: safety culture; organizational culture; patient safety; safety management; Covid-19